(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article considering linguistic and didactic notions that are considered to be background for researching - <culture of Speech? , speech communication quality, performance qualities of a perfect speech. Particular attention is paid to disclosure of communication language and thinking, language and speech, Culture Broadcasting, and general culture of the individual as an indicator of personal self-development.